Environmental & architectural phenomenology. Vol. 6, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 1995)
Vol. 6, No. 3, Fall 1995 (includes “items of interest,” "citations received,” book reviews of Chris Cokinos & Louise Chawla's The First Country of Places & Edward Relph's The Geography of Nowhere, and essays by Carolyn Prorok & Doug Paterson).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals